2020
DOI: 10.9740/mhc.2020.07.215
|View full text |Cite
|
Sign up to set email alerts
|

Does early physical therapy intervention reduce opioid burden and improve functionality in the management of chronic lower back pain?

Abstract: Abstract Introduction Chronic lower back pain is a leading cause of disability in US adults. Opioid use continues to be controversial despite the Centers for Disease Control and Prevention guidance on chronic pain management to use nonpharmacologic and nonopioid pharmacologic interventions. The objectives of the study were to assess the impact of early physical therapy (PT) intervention on im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…There is increasing evidence that in LBP patients, exercise alone or exercise in combination with education programs can reduce the risk of a future episode of LBP as well as future LBP intensity [ 25 , 26 ]. Additionally, a recent study showed that early physiotherapy significantly improves functionality and reduces pain in patients with chronic LBP [ 15 ], highlighting the importance of physiotherapy in the initial treatment of LBP. As our results show changes in volume and degeneration of lumbar and trunk musculature of LSTV patients, which may be caused by or may cause the development of LBP, exercise and physiotherapy need to be considered important strategies in pain prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that in LBP patients, exercise alone or exercise in combination with education programs can reduce the risk of a future episode of LBP as well as future LBP intensity [ 25 , 26 ]. Additionally, a recent study showed that early physiotherapy significantly improves functionality and reduces pain in patients with chronic LBP [ 15 ], highlighting the importance of physiotherapy in the initial treatment of LBP. As our results show changes in volume and degeneration of lumbar and trunk musculature of LSTV patients, which may be caused by or may cause the development of LBP, exercise and physiotherapy need to be considered important strategies in pain prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that atrophy of paraspinal muscles may lead to altered thoracic kyphosis, lumbar lordosis, and sacralvertebral angles both in adults with and without degenerative spinal disease [12][13][14]. Due to this important role trunk and lumbar muscles play in spinal integrity and pain development, physiotherapy has been shown to significantly improve functionality and positively alter the course of LBP [15].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with LBP were at significant risk for physical and mental health deterioration, due to the lack of clinical and self-management resources and pandemic-related stressors. 17 - 19 A large proportion of patients with LBP can be managed conservatively, 13 do not require imaging, 13 , 20 will have a normal neurological exam, 21 , 22 and benefit from a personalized home exercise program with education, guidance, and strategies for self-management. 22 , 23 This evidence supported the potential to utilize virtual care (VC) to assess and manage this patient population, when in-person assessment and management was very limited.…”
Section: Introduction/objectivesmentioning
confidence: 99%
“…The prevalence of analgesic intake for CSP varies across the literature, with some studies demonstrating very high levels (80%-100%) [ 31 , 69 ], while others report values in line with this study [ 26 ]. PT can contribute to a reduction in analgesic intake [ 70 , 71 ]. In this study, the low proportion of patients receiving pharmacological treatment at baseline (DGPT: 2/41, 4.9% and CG: 7/41, 17.1%) limited the statistical assessment of this aspect.…”
Section: Discussionmentioning
confidence: 99%